2005
DOI: 10.1016/j.jcrs.2004.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of mechanical anisotropy in the cornea and sclera

Abstract: The mathematical model described appears to provide a framework for further development, capturing the essential features of mechanical anisotropy of the cornea. The tunnel incision simulation indicated the importance of the anisotropy in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
178
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 9 publications
1
178
1
1
Order By: Relevance
“…An initial global study of the error as a function of {α, β, µ} showed insensitivity to µ and consequently µ was set to 10.0kP a (the same order of magnitude as cited in [69] for human corneas). (See [76] for a complete sensitivity analysis of the QLV framework).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial global study of the error as a function of {α, β, µ} showed insensitivity to µ and consequently µ was set to 10.0kP a (the same order of magnitude as cited in [69] for human corneas). (See [76] for a complete sensitivity analysis of the QLV framework).…”
Section: Resultsmentioning
confidence: 99%
“…Following [69], the fibril strain-energy function, W f ibrils , is determined by integrating contributions of individual fibrils w f ibril…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method allows the use of a black box structural solver if the finite element code is able to update the initial stress tensor field with each iteration [19]. A similar approach of prestressing was used earlier by Pinsky et al to include the internal stress state in the cornea under the presence of the full intraocular pressure load through a fixed point iteration instead of increasing the pressure incrementally [20].…”
Section: Existing Solution Methods and Limitationsmentioning
confidence: 99%
“…The factor in parenthesis is the pull-back of the fluid pressure through the motion to the reference configuration. For anisotropic porous materials, examples of the strain energy density function W can be found in Gasser et al (2006) and Pinsky et al (2005). The relationship between the total Cauchy stress tensor in equation (6) and the second Piola-Kirchhoff stress tensor in equation (7) is given by…”
mentioning
confidence: 99%